Diagnosing giant cell arteritis: a comprehensive practical guide for the practicing rheumatologist. (13th July 2021) - Andel, Peter M; Chrysidis, Stavros; Geiger, Julia; Haaversen, Anne C Bull; Haugeberg, Glenn; Myklebust, Geirmund; Nielsen, Berit D; Diamantopoulos, Andreas P
Abstract: GCA is the most common large vessel vasculitis in the elderly population. In recent years, advanced imaging has changed the way GCA can be diagnosed in many locations. The GCA fast-track clinic approach combined with US examination allows prompt treatment and diagnosis with high certainty. Fast-track clinics have been shown to improve prognosis while being cost effective. However, all diagnostic modalities are highly operator dependent, and in many locations expertise in advanced imaging may not be available. In this paper, we review the current evidence on GCA diagnostics and propose a simple algorithm for diagnosing GCA for use by rheumatologists not working in specialist centres.